9. Römerquelle - Kunstwettbewerb 1989. - Kulturzentrum Reitschulgasse 4, Klagenfurt; Neue Galerie der Stadt Linz; Galerie im Taklhaus, Salzburg; Galerie Stabenbastei, Wien; Wiener Secession, Wien (Wien : Römerquelle G.m.b.H., 1989)
Hoffmann, Guido ; Blank, Michael ; Fian, Helmut ; Reiterer, Werner ; Schuster, Michael ; Doppler, Horst Maria ; Dorfer, Oliver ; Stifter, Wolfgang ; Nussbaumer, Günther ; Sasshofer, Brigitte ; Hofmeister, Werner ; Wid, Udo
9. Römerquelle - Kunstwettbewerb 1989, Kulturzentrum Reitschulgasse 4, Klagenfurt, 15. Juni - 1. Juli 1989 ; Neue Galerie der Stadt Linz, 7. Juli - 9. September 1989 ; Galerie im Taklhaus, Salzburg, 12. Oktober - 4. November 1989 ; Galerie Stabenbastei, Wien, Oktober - November 1989 ; Wiener Secession, Wien, 10. November - 10. Dezember 1989
boek